2014
DOI: 10.1177/0047287514522873
|View full text |Cite
|
Sign up to set email alerts
|

Localizing Cultural Values on Tourism Destination Websites

Abstract: The present study contributes to the current localization literature by revealing the effects of localizing cultural values on tourism destination websites on users’ destination image and willingness to travel. Reporting on two tests, the first is an analysis of the depiction of cultural values on 48 New Zealand, 36 Indian, and 46 Chinese destination sites. Results indicate significant differences in the cultural values exposed among the three countries. The second study reports on an experiment requiring 400 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 100 publications
2
38
0
1
Order By: Relevance
“…This understanding is of particular interest in the international market as tourists' evaluations are influenced by cultural variations. These results are in line with those of earlier works that underline the need to adapt sales platforms appropriately, to better reflect the needs and specificities of target markets (Tigre, Gnoth, and Deans 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This understanding is of particular interest in the international market as tourists' evaluations are influenced by cultural variations. These results are in line with those of earlier works that underline the need to adapt sales platforms appropriately, to better reflect the needs and specificities of target markets (Tigre, Gnoth, and Deans 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Since the 1980s, various researchers have debated the most appropriate choice of dimensions to conceptualize culture (e.g., Hofstede 1980;Keillor and Hule 1999;Steenkamp 2001). However, it is the framework developed by Hofstede (1980) and Hofstede, Hofstede, and Minkov 2010) that has become established as the most dominant and influential cultural paradigm (Sivakumar and Nakata 2001;Steenkamp 2001;Tigre, Gnoth, and Deans 2014). Hofstede defines national culture as "the programming of the mind which distinguishes the members of one group or category of people from another".…”
Section: National Culturementioning
confidence: 99%
“…American Facebook site operators wrote: "Our very own Chef Dan made an appearance on Good Morning America this morning (September 5th). Fifth, Taiwanese site operators often market their products with the direct and hard approach, which emphasizes the use of direct and confrontational appeals in forms of discounts and sale promotions [11] [17], with the words such as super value (chāo zhí), great value (yōu huì), half-price (bàn jià), coupons (yōu huì quàn), and buy one get one free (mǎi yī sòng yī). Also, Taiwanese operators tended to specifically indicate the price of their products (mài cuì jī zhī yào + $29) to market their products.…”
Section: Site Operators' Postingsmentioning
confidence: 99%
“…Compared with the direct and hard-sell approached adopted by the Taiwanese site operators, the American McDonald's site operators sell their products in a more indirect and soft way, which emphasizes a more suggestive and a softer emotional appeal with the focus on emotions, sentiments and entertainment [11] [17]. For example, they described their French fries as "Golden rays of light" (posted on July 7th), and promoted their company products writing "Falling for the Golden Arches" (posted on November 17th).…”
Section: Site Operators' Postingsmentioning
confidence: 99%
“…In addition, some authors [19,20] have suggested that tourist preferences are influenced by the heritage and cultural elements in destinations, despite the existence of other significant attributes that are unrelated to these. This influence of cultural elements can occur even before the visit, through the image created by tourism destination websites [21].…”
Section: Introductionmentioning
confidence: 99%